Manpower Planning, Work Environment and Service Delivery in Ogun State Hospital Management Board - Olanipekun, Lateef Okikiola (Zien Journals, 2021)
The problematic situation of developing societies to retain their medical personnel given their inability to institute viable manpower plan and conducive work environment that should be suitable for the fulfillment of the lofty aspirations of medical personnel is what necessitates the study. Hence, the study investigated the relationship between manpower planning, work environment and service delivery in Ogun State Hospital Management Board (OGHMB). Three hypotheses were formulated and tested for the study. The main instrument used for this study was questionnaire and interview administered medical and non-medical personals of the board randomly selected from ten hospitals in five zones in Ogun State. This study adopted both quantitative and qualitative research designs, while Product Moment Correlation Coefficient (r) and regression to test the stated hypotheses
Keywords: regression; developing; manpower; environment